Pyrophosphate and Irreversibility in Evolution, or why PPi Is Not an Energy Currency and why Nature Chose Triphosphates - Wimmer, Jessica L. E.; Kleinermanns, Karl; Martin, William F. (Frontiers in Microbiology, 2021)
The possible evolutionary significance of pyrophosphate (PPi) has been discussed since the early 1960s. Lipmann suggested that PPi could have been an ancient currency or a possible environmental source of metabolic energy at origins, while Kornberg proposed that PPi vectorializes metabolism because ubiquitous pyrophosphatases render PPi forming reactions kinetically irreversible. To test those ideas, we investigated the reactions that consume phosphoanhydride bonds among the 401 reactions of the universal biosynthetic core that generates amino acids, nucleotides and cofactors from H2, CO2 and NH3. We find that 36 % of the core’s phosphoanhydride hydrolyzing reactions generate PPi, while no reactions use PPi as an energy currency. The polymerization reactions that generate ~80 % of cell mass—protein, RNA and DNA synthesis—all generate PPi while none use PPi as an energy source. In typical prokaryotic cells, aminoacyl tRNA synthetases (AARS) underlie ~80 % of PPi production. We show that the irreversibility of the AARS reaction is a kinetic, not a thermodynamic effect. The data indicate that PPi is not an ancient energy currency and probably never was. Instead, PPi hydrolysis is an ancient mechanism that imparts irreversibility, as Kornberg suggested, functioning like a ratchet's pawl to vectorialize the life process towards growth. The two anhydride bonds in nucleoside triphosphates offer ATP-cleaving enzymes an option to impart either thermodynamic control (Pi formation) or kinetic control (PPi formation) upon reactions. This dual capacity explains why nature chose the triphosphate moiety of ATP as biochemistry's universal energy currency.